2022
DOI: 10.1155/2022/4773395
|View full text |Cite
|
Sign up to set email alerts
|

Container Ship Carbon and Fuel Estimation in Voyages Utilizing Meteorological Data with Data Fusion and Machine Learning Techniques

Abstract: The International Maritime Organization (IMO) had made effort to reduce the ship’s energy consumption and carbon emission by optimizing the ship’s operational measures such as speed and weather routing. However, existing fuel consumption models were relatively simple without considering the quantified effect of weather conditions. In this paper, a knowledge-based ridge regression-based algorithm is presented for enabling automated fuel consumption estimation under varying weather conditions during voyages. Win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As such, numerical methods were employed to predict ship power in order to discover the substantial demand for FOC under different navigational conditions by means of data-driven machine learning methods [18]. Studies by Ren et al [19] also reveal the consistency of utilizing AIS data for FOC estimation in way of predicting ship emissions, compared to direct reference on daily fuel oil measurement data. Similarly, Kaklis et al [4] also demonstrated FOC estimation by a deep-learning model (SplineLSTM) to reflect the associated emissions of a ship.…”
Section: Related Workmentioning
confidence: 99%
“…As such, numerical methods were employed to predict ship power in order to discover the substantial demand for FOC under different navigational conditions by means of data-driven machine learning methods [18]. Studies by Ren et al [19] also reveal the consistency of utilizing AIS data for FOC estimation in way of predicting ship emissions, compared to direct reference on daily fuel oil measurement data. Similarly, Kaklis et al [4] also demonstrated FOC estimation by a deep-learning model (SplineLSTM) to reflect the associated emissions of a ship.…”
Section: Related Workmentioning
confidence: 99%
“…And the results showed that ANN has a higher prediction accuracy than the polynomial regression and support vector machine in fuel consumption prediction [6]. Ren compared the prediction results under different data sources using a ridge regression model based on AIS data, MRV data, and MRV-normalized data, respectively, and found that the model based on MRV report achieved the best results [7]. Li investigated the results of various prediction models with different combinations of data sources based on a variety of data sources, such as logbooks, meteorological data, and AIS data [8][9][10].…”
Section: Related Workmentioning
confidence: 99%
“…Various machine learning algorithms that have been utilized in the attempt to develop the FOC prediction model include linear regression [20], multiple linear regression [21], ridge regression [22], support vector regressor [23], lasso regression [24], K-nearest neighbor regressor [25], extra tree regressor [26], random forest regressor [27], Gaussian process metamodel [28], artificial neural network (ANN) approach [29], and even deep learning [30]. Traditional methods, such as statistical analysis, have initially been used to examine historical consumption patterns, identify key factors influencing consumption, and develop predictive models, but these methods have been found to have low accuracy [31].…”
Section: Existing Researchmentioning
confidence: 99%